Ghost cells: A journey in the dark... - Monica Mehendiratta; Kundendu A Bishen; Karen Boaz; Yulia Mathias (Wolters Kluwer Medknow Publications, 2012)
Ghost cells have been a topic of controversy since a long time. The appearance of these cells in different lesions has given it varying terms. In lesions like that of Calcifying cystic odontogenic tumor (CCOT), these cells have been termed as 'Ghost cells' whereas similar descriptive cells have been called shadow/translucent cells in non-odontogenic lesions like Craniopharyngiomas of the pituitary gland and Pilomatricomas of skin. Controversy arises because of the fact that there are varying opinions and incomplete knowledge about their origin, nature, significance and relation in different neoplasms. Irrespective of the origin, these cells are seen in odontogenic and non-odontogenic neoplasms, which probably direct us towards a missing link between these differing neoplasms. This article attempts to present a review on the concepts around these peculiar cells and shed some light on these ghosts that are still in dark.